REDEFINISI PUBLICNESS DALAM RUANG LINGKUP ADMINISTRASI PUBLIK DI INDONESIA - Izzul Fatchu Reza (Yogyakarta State University, 2016)
The term publicness which often stated in many literatures and public adminstration scientific discussion was originated from Western nations’ scholar nomenklatur. In its implementation in Indonesia, publicness has already been practiced since long time ago, even it rooted back to the nation founding. This papers aimed to identify the practice of publicness in Indonesia and its redefinition in the context of state administration. This study uses literature study approach. The result of the research showed that the public spirit, or the publicness has been actualized in the concept of people’s rule, the discussion to reach consensus, and the establishment of Development Plan Meeting (Musrenbang). In its implementation in Indonesia, the political term used by Bozemann in interpreting the publicness definition must be cleared, become the political authority that allocate some public goods and belongs to citizen interest.Keywords: Publicness, Public Interest, Public Administration